2012
DOI: 10.1039/c2cc34745h
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic self-healing hydrogel

Abstract: A straightforward method to prepare a novel magnetic self-healing hydrogel has been successfully developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
211
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 291 publications
(212 citation statements)
references
References 27 publications
0
211
0
1
Order By: Relevance
“…Other uses are, e.g., to give a temporary tissue support in cataract surgery or controlled release of various types of drugs and biomolecules [11,12] and in an interesting combination with Fe3O4 affording a magnetic self-healing hydrogel [13][14][15]. The properties of chitosan, physical and biological, have made it a promising candidate for delivery of pharmaceutically active components and as a delivery vehicle for, e.g., vaccines [16,17], gene fragments [18] and micro-RNA [19].…”
Section: Open Accessmentioning
confidence: 99%
“…Other uses are, e.g., to give a temporary tissue support in cataract surgery or controlled release of various types of drugs and biomolecules [11,12] and in an interesting combination with Fe3O4 affording a magnetic self-healing hydrogel [13][14][15]. The properties of chitosan, physical and biological, have made it a promising candidate for delivery of pharmaceutically active components and as a delivery vehicle for, e.g., vaccines [16,17], gene fragments [18] and micro-RNA [19].…”
Section: Open Accessmentioning
confidence: 99%
“…Hydrogel passes through a channel with an obstacle in themiddle by shape transformation under the assistance of a N45 magnet [36] Fu 等 [37] S: CPS biohybrid, C1: chitosan-silica hybrid, C2: chitosan-PEG xerogel, C3: chitosan monoliths, and C4: porous silica 二醇修饰物作为网络结构交联剂也被证明具有良好的 生物相容性. 同时, 亚胺键的动态化学平衡使得材料具 有多重响应的特性, 可应用于开发多功能智能水凝胶材 料.…”
Section: Figureunclassified
“…It was recently reported that magnetic Fe 3 O 4 nanoparticles with a carboxyl group on its surface were immobilized in chitosan and then formed hydrogel with telechelic difunctional poly(ethylene glycol) (DF-PEG) via imine bonds [27]. The self-healing performance of the hydrogel relied on the dynamic equilibrium of the bond breaking and reforming in the damaged region.…”
Section: Functional Self-healing Materialsmentioning
confidence: 99%